Les jardins collectifs ont-ils droit de cité ? - Bruno Marmiroli (In Situ)
Collective gardens, a term which covers many different types of gardens, raise new issues around the environment, social links, exchanges and the protection of ‘ordinary’ nature in metropolitan territories. These gardens are often initiated by spontaneous collective aspirations which ignore public policies. But they become institutionalised spaces once the local authorities take over responsibility for them. Although they may feature in politicians’ declarations, they rarely feature in urban projects, particularly where space is subjected to intense real estate pressure. These collective gardens then do not enjoy the protection they deserve in view of the services they provide. By taking a new look at the history of family gardens, which enjoy some measure of recognition, this article proposes further measures that might be studied in order to better integrate collective gardens into urban projects. Several approaches are considered, the first looking at legal measures that could give these gardens specific statutory protection that would limit their precarity. The second approach looks at the developing movement for urban ecology, in which the garden has an important role to play, despite the difficulties of introducing it to town-planning tools. The last orientation is founded on an extension of our notions of heritage in order to encompass the collective garden as a king of median space between nature and culture.